"Composer Refat Ibadlaev" - Bahadirov Nail Sharifovich (Genius Journals, 2022)
The article highlights the work of the composer Ibadlaev Refat Ibadlaevich, who lived and worked for many years in the city of Gulistan, The Republic of Uzbekistan. The composer made a significant contribution and significantly enriched the concert repertoire of accordionists with his original compositions and arrangements for this wonderful instrument of Crimean Tatar melodies and plays by composers of Uzbekistan. The second part of the article offers a brief analysis and musical text of the plays: "Ekspromt in E Minor", "Bayram Khaytarmasi", "Paraphrase on the theme of F. Kadyrov's dance", "Paraphrase on two Uzbek folk themes"
Keywords: Composer; creation; button accordion; treatment